Concentrations of TSP-Bound Metals in Four Urban Residential Locations in Seoul, Korea - Hang Thi Nguyen; Chan Goo Park; Jin-A Kim; Je-Seung Lee; Jin-Hong Lee; Ki-Hyun Kim (The Scientific World Journal)
Concentrations of 17 trace metals bound in total suspended particulate (TSP) were measured at four urban residential locations (Jong Ro [JR], Gwang Jin [GJ], Gang Seo [GS], and Yang Jae [YJ]) in Seoul, Korea from February to July 2009. The maximum concentrations of metals were recorded by Fe in the range of 2599 (JR) to 2914 ng m-3 (GJ), while the least values were observed from Ag or Co with a few ng m-3. The relative ordering of the mean concentration (ng m-3) at these sites is generally found on the order of Fe > Zn > Ba > Mn > Pb > Cu > B > Cr > Ni > Sr >V > As > Li > Cd > Mo > Co > Ag or with a few exceptions (e.g., a reversal between Ba and Mn or between Ni and Sr). Calculation of the enrichment factor suggests the significant role of man-made processes on such metals as Cd, Zn, and Pb. Inspection of the temporal patterns indicates the peak occurrence of most metals during the spring season due in part to the Asian Dust (AD) event. However, according to the factor analysis, sources of these metals were dominated by both resuspended soil/road dust and the combustion of fossil fuels. The overall results of our study suggest that the interaction between the environmental conditions and roadside traffic activities are paramount in explaining the metal pollution in these urban residential areas.